Studies on the Charge-TransferInteraction Between TamoxifenCitrate and Chloranilic Acid: Charge-transfer between tamoxifen and chloranilic acid - Sinyeofori A. Brown; Ekaete I. Akpabio; Paul A. Akpa; Petra O. Nnamani; Bertrand C.Akabuogu; Godswill C. Onunkwo (Iranian Journal of Pharmaceutical Sciences, 2007)
The complex formed as a consequence of the interaction between the electron-acceptor P-chloranilic acid and an electron donor tamoxifen citrate was employedin the assay of the drug in pure powder and tablets. Chloranilic acid was found toform a charge-transfer complex in a 1:1 stoichiometric ratio, with tamoxifen citrate.The wavelength of maximum absorption for the complex was found to be 550 nmwhile the absorbance was linear over the concentration range of 2-100 g/ml.Evaluations of the various thermodynamic parameters by means of the Scottequation was carried out and were found to decrease with increase in temperature.The free energy change (ΔG°) and the enthalpy of formation (ΔH°) as well as theentropy (ΔS°) were determined for various interactions. Results obtained suggestthat the proposed method may be conveniently applied in the analysis ofcommercially available tamoxifen citrate tablets with a high degree of accuracy andreproducibility.